Genome Skimming Reveals Widespread Hybridization in a Neotropical Flowering Plant Radiation - Loiseau, Oriane; Mota Machado, Talita; Paris, Margot; Koubínová, Darina; Dexter, Kyle G.; Versieux, Leonardo M.; Lexer, Christian; Salamin, Nicolas (Frontiers in Ecology and Evolution, 2021)
The tropics hold at least an order of magnitude greater plant diversity than the temperate zone, yet the reasons for this difference are still subject to debate. Much of tropical plant diversity is in highly speciose genera and understanding the drivers of such high species richness will help solve the tropical diversity enigma. Hybridization has recently been shown to underlie many adaptive radiations, but its role in the evolution of speciose tropical plant genera has received little attention. Here, we address this topic in the hyperdiverse Bromeliaceae genus Vriesea using genome skimming data covering the three genomic compartments. We find evidence for hybridization in ca. 11% of the species in our dataset,both within the genus and between Vriesea and other genera, which is commensurate with hybridization underlying the hyperdiversity of Vriesea, and potentially other genera in Tillandsioideae. While additional genomic research will be needed to further clarify the contribution of hybridization to the rapid diversification of Vriesea, our study provides an important first data point suggesting its importance to the evolution of tropical plant diversity.